Realizing surface amphiphobicity using 3D printing techniques: A critical move towards manufacturing low-cost reentrant geometries - Shams, Hamza; Basit, Kanza; Khan, Muhammad Ali; Saleem, Sajid; Mansoor, Asif (Elsevier, 2021)
Amphiphobic surfaces are obtained by lowering the surface energy through changes in surface geometry. These changes can be designed on the surface, thereby altering its wettability, and in turn rendering it amphiphobic. The main geometrical entities behind this phenomenon are reentrant geometries which prevent the solid-liquid interface tension from breaking, thereby resulting in contact angles greater than 90°. The science behind modelling and manufacturing of these reentrant geometries is well established apart from manufacturing them via extrusion-based 3-Dimensional printing processes. This review paper in identifying this gap summarizes various characterization parameters for surface wettability followed by identifying the role of surface reentrant geometries to introduce superamphiphobicity in polymers. The focus of the paper then moves towards achieving amphiphobicity using 3D printing processes where the current state of research is discussed in terms of reentrant profiles and achievement of high static contact angles. Role of the most common yet rarely reported Fused Deposition Modelling technique is discussed in more detail and a preliminary investigation based on characteristics flow and printing parameters used in Fused Deposition Modelling has been presented. The surface amphiphobicity is achieved in a one-step process characterized by high static contact angles with low and high surface tension liquids owing to air entrapment in characteristic layer-by-layer deposition features obtained in Fused Deposition Modelling.
Keywords: Wetting angle; 3D printing; Amphiphobicity in polymers; Reentrant geometry